SubEdPro: Subtitle Editor Professional - Ahmad Nawir, Nur Adilah Adha; Ibrahim, Rosziati (Applied Information Technology And Computer Science, 2025)
There are various subtitle editors available on the Internet. Subtitle Editor Professional is a new subtitle editor tool developed to tackle the problem of the existing subtitle editor, which is not user-friendly, has a lot of components, and has limitations. The limitation is that there is no function to change the animation speed, a limited animation direction, and no encoding function. The objectives of this project are to analyze and design the SubEdPro by using the UML specification, to develop the SubEdPro by using object-oriented programming, and to test the SubEdPro by using alpha and beta testing. SubEdPro was developed using the PHP, HTML and JavaScript languages. The development of SubEdPro is expected to be able to solve the problem of the existing subtitle editor. Through this tool, users can have a better experience when typesetting the subtitles and reduce the time consumed, as timing the subtitles is already time-consuming.